2007
DOI: 10.1212/01.wnl.0000252801.61190.e8
|View full text |Cite
|
Sign up to set email alerts
|

The burden of inpatient neurologic disease in two Ethiopian hospitals

Abstract: Patients with neurologic disease make up a substantial minority of medical inpatients in Ethiopia. Noninfectious neurologic disease is at least as common as infectious neurologic disease. Reaching a well-defined final diagnosis occurs in only a minority of cases. Areas for improving the mortality rate include improving the barriers to diagnostic certainty and increasing treatment options for Ethiopian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 7 publications
11
56
0
Order By: Relevance
“…Previous studies conducted in Tanzania demonstrated a huge diff erence in the apparent incidence of stroke when comparing rural and urban settings (4.5% [9] and 25% [10] of all neurological admissions). However, Bower et al (2007) observed only minor diff erences (rural 16.2% and 21.8% urban) [5]. Th e present analysis also appears to indicate a signifi cantly larger percentage of stroke patients in the urban catchment area; however, diff erences being less pronounced.…”
Section: Vascular Diseasesupporting
confidence: 41%
See 2 more Smart Citations
“…Previous studies conducted in Tanzania demonstrated a huge diff erence in the apparent incidence of stroke when comparing rural and urban settings (4.5% [9] and 25% [10] of all neurological admissions). However, Bower et al (2007) observed only minor diff erences (rural 16.2% and 21.8% urban) [5]. Th e present analysis also appears to indicate a signifi cantly larger percentage of stroke patients in the urban catchment area; however, diff erences being less pronounced.…”
Section: Vascular Diseasesupporting
confidence: 41%
“…Th is is particularly striking in rural African catchment areas where only very sparse data are available with previous neurological prevalence studies in rural areas lacking the crucial diagnostic feature of cross-sectional imaging [3][4][5]. Consecutively the present survey allows for the fi rst time a comparison between the disease pattern of cranial pathologies in a rural and an urban setting of eastern Africa.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Neurological disorders explained 3% of global disability-adjusted life-years (DALYs) and 5.6% of global years lived with disability [5]. In 2005, neurological disorders contributed to 92 million DALYs and are expected to increase to 103 million in 2030 [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…HIV or TB infection) [2,3] . Several recent hospital-based studies from Africa document that neurological disorders account for 18-25% of medical admissions, suggesting a much heavier burden of disease in the community than reported by the GBDS [4][5][6][7] . The only three population-based assessments of adult neurological disease in Africa predated the HIV epidemic [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%